Gastroenterologists Reveal More Digestive Symptoms in COVID-19 Patients than Nongastroenterologists in Fever Clinic - Yudong Jiang; Chaoqun Han; Tao Bai; Shengyan Zhang; Jun Song; Xiaohua Hou (Gastroenterology Research and Practice)
The incidence of digestive symptoms may vary depending on doctors’ professional backgrounds when they inquired suspected COVID-19 patients in a fever clinic. We sought to understand the characteristics of inquiries about digestive symptoms by doctors in different specialties; therefore, inquiry records of 2 gastroenterologists and 6 nongastroenterologists were reviewed. We compared the difference in inquiry of digestive symptoms (diarrhea, vomit, distension, anorexia, and abdominal pain) between these two groups among identified COVID-19 patients. And we further compared the difference of digestive symptoms between confirmed patients and suspected cases who excluded from COVID-19. Among 495 confirmed COVID-19 cases (254 cases by gastroenterologists and 241 cases by nongastroenterologists), 22.83% patients experienced various digestive symptoms in the gastroenterologists’ group, while only 4.47% reported digestive symptoms by nongastroenterologists (p<0.0001). Additionally, among initially suspected 611 patients who presented with similar respiratory symptoms inquired by gastroenterologists, confirmed cases presented far more frequency of digestive symptoms than excluded cases (22.8% vs. 3.64%, p<0.0001). Furthermore, confirmed patients reported more percentage of watery diarrhea (56% vs. 36%, p<0.0001) and higher frequent vomit (2.77±0.97 vs. 1.80±0.45 per day, p=0.041) than excluded cases. We concluded that gastroenterologists could detect a greater proportion of gastrointestinal symptoms in COVID-19 patients during fever clinic inquiries. Moreover, confirmed COVID-19 patients are more likely to have higher severity in digestive symptoms than excluded cases. Therefore, physicians in fever clinic should pay more attention to the triage of gastrointestinal symptoms.